Nutrition Induced Remodeling Dynamics of Cell Membranes: Implications for Performance, Health, and Welfare Issues in Food Animals - Md. Emran Hossain (International Journal of Membranes, 2026)
Cell membranes represent dynamic structural and functional platforms that integrate nutritional signals with cellular metabolism, immune competence, and physiological adaptation in food animals. Beyond their classical role as selective barriers, membranes actively regulate nutrient transport, signal transduction, and bioenergetics through highly responsive lipid and protein networks. Dietary components, particularly fatty acids, vitamins, minerals, amino acids, and bioactive compounds, critically influence membrane composition, fluidity, and stability, thereby shaping cellular function and systemic performance. Nutrition induced membrane remodeling operates through coordinated mechanisms involving lipid turnover, oxidative balance, and microbiota mediated metabolic interactions, which collectively determine membrane resilience under physiological and environmental stress. These remodeling processes exert profound effects on mitochondrial efficiency, gut barrier integrity, immune responsiveness, and neurocellular plasticity, linking membrane biology directly to growth efficiency, feed conversion, thermoregulation, health outcomes, and animal welfare. Emerging evidence highlights that targeted nutritional strategies can mitigate oxidative membrane damage, enhance disease resistance, and improve behavioral and stress related responses, particularly in intensive production systems. Advanced methodological approaches including lipidomics, biophysical imaging, and biomarker profiling now enable deeper characterization of membrane dynamics and their nutritional modulation. Despite significant progress, critical knowledge gaps remain regarding tissue specific remodeling patterns, long term functional consequences, and translational applicability under commercial farm conditions. This review synthesizes current mechanistic and applied insights into nutrition driven membrane remodeling in food animals, emphasizes its relevance for sustainable and welfare-oriented production, and outlines future directions including integrative multiomics and precision nutrition approaches aimed at optimizing membrane function for improved productivity and health.
Keywords: animal Welfare; cell membranes; gut barrier; lipidomics; membrane fluidity; precision nutrition; sustainable production